Suppression of human CD4+ T cell activation by 3,4-dimethoxycinnamonyl-anthranilic acid (tranilast) is mediated by CXCL9 and CXCL10 - Berberich, Anne; Bunse, Theresa; Litzenburger, Ulrike; Opitz, Christiane; Falk, Christine Susanne; Serafini, Tito; Wick, Wolfgang; Platten, Michael (Biochemical pharmacology, 2011)
3,4-dimethoxycinnamonyl-anthranilic acid (tranilast) is an orally available anti-allergic drug with structural and functional homologies to immunosuppressive catabolites of the essential amino acid tryptophan and broad anti-inflammatory properties. It has recently been shown to be effective in animal models of multiple sclerosis and rheumatoid arthritis, two autoimmune diseases that are mediated by auto-aggressive Th1-polarized CD4+ T lymphocytes. Here we demonstrate potent suppressive effects of tranilast on the function of naïve human CD4+ T cells. Tranilast inhibited inhibits activation and proliferation of purified CD4+ T cells stimulated through the T cell receptor with an EC50 of less than 10μM, a concentration that is well below plasma levels achieved after oral administration of approved doses of 200-600mg in humans. The antiproliferative effects were less potent on naïve CD8+ T cells. Suppression of CD4+ and CD8+ T cell proliferation was associated with an inhibition of T cell activation. Cytokine analyses of naïve CD4+ T cells revealed that tranilast interferes with the production of cyto- and chemokines driven by signal transducer and activator of transcription 1 (STAT1), notably chemokine (C-X-C motif) ligands (CXCL) 9 and 10. Tranilast limited STAT1 phosphorylation in activated T cells and supplementation of CXCL9 or CXCL10 reversed the anti-proliferative effects of tranilast. These data imply CXCL9 and CXCL10 as novel therapeutic targets of tranilast in Th1-mediated autoimmune diseases and identify phospho-STAT1 and its target chemokines CXCL9 and CXCL10 as potential markers for monitoring the bioactivity of tranilast in humans.
Gesehen am 05.10.2022